(untitled) (Pravaha, 2018)
Pottery is unique art of making artifacts from clay. It produces different kinds of clay and ceramics items such as flowerpots, water and grain storage jars, large vessels for distilling rice spirits called rakshi, cooking pots, tableware, stoneware cups, bowls, and plates, stoneware pitcher and mug, etc. This research aims to examine challenges faced by the pottery industries and to examine scopes of the pottery industries in Nepal. This research is based on the descriptive method. The results show that there is good scope in the this industry but the people involved in this industry are facing different kinds of challenges or problems like shortage of raw materials, manpower, and lack of space to dry the formed pottery, firing pottery, to store the finished goods along with the different raw materials. The sales of the product in the national and international markets are being increased. This industry is being affected by the change in lifestyle and different substitute products. The intermediaries get good profits but they face the problem of getting the products damaged, demand dependent on the festive occasion, problem of transportation, etc. Study shows that there is a huge demand for Nepali handmade ceramic products in the international market due to their improved quality. Buyers are willing to pay a premium for handmade goods, which are propelling exports. Pravaha Vol. 24, No. 1, 2018, Page: 147-158